Rekontruksi Profesionalisme Auditor: Perspektif Moral Reasoning dan Qs. Al-Isra (36) dalam Mengungkap Fraud - Siti Nurhaliza (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to explain and reconstruct the notion of auditor professionalism beyond the reasoning framework found in the accountants’ code of ethics. The reconstruction is carried out by redefining auditor professionalism through the integration of moral reasoning and the values derived from QS. Al-Isra (36), as a response to the issue of fraud disclosure. The research adopts a non-technical perspective on auditor professionalism. Accordingly, the appropriate method for this study is Theoretical Triangulation, namely testing auditor professionalism from the perspective of moral reasoning and QS. Al-Isra (36). Specifically, the research begins by utilizing three sources of values: the Handbook of the Code of Ethics for Professional Accountants, principles of moral reasoning, and the guidance in QS. Al-Isra (36). Second, the study identifies the limitations of conventional interpretations of auditor professionalism when examined solely from ethical codes, and further analyzes how moral reasoning and QS. Al-Isra (36) enrich this perspective. Third, the concept of auditor professionalism is reconstructed in a holistic manner. Finally, the study concludes whether moral reasoning and QS. Al-Isra (36) are interrelated with the auditors’ professionalism in uncovering fraud. Ultimately, this article proposes a revised conception of auditor professionalism. By incorporating moral reasoning and QS. Al-Isra (36), auditor professionalism is envisioned as transcending rationalism and materialism. It is defined as a commitment to uphold the accountants’ code of ethics, grounded in justice and virtue, with an awareness that every action will be held accountable in the hereafter.